The Effect Of Overburden On Pile Capacity In A Calcareous Marl - William M. Camp (Deep Foundations Institute, 1993)
An extensive design phase testing program in which 10 piles and 2 drilled shafts were instrumented and statically load tested to failure, was undertaken to establish relevant foundation design parameters for two bridges in Charleston, South Carolina, USA. The bearing strata at both test sites was a calcareous, overconsolidated, firm to very stiff, slightly sandy, clayey silt (locally known as Cooper Marl). Confirmation dynamic and static loading tests on production piles indicated only 50 to 60% of anticipated pile capacities; including consideration of time effects. Supplemental subsurface explorations did not reveal any significant variations in marl properties. Ultimately, 22 static and 75 dynamic tests were performed on production piles for a 2 mile section of the project. Pore water pressures in the marl were also monitored during and after pile driving. A study of unit skin friction in the marl as a function of time revealed two distinct trends: piles driven in areas with a sand overlaying the marl gained more capacity significantly faster than those driven through a clay or silt. Although the insitu marl properties are apparently similar across the site, the material immediately above the marl evidently has a large effect on pile capacity. This effect of overburden on pile capacity was verified by testing piles over a period of two years.